From the Antenna to the Display Devices: Transformation of the Colombian Radio Industry - Barrios-Rubio, Andrés (Journalism and Media, 2021)
Consolidation of the digital environment has become an irreversible global reality and, for the Colombian radio industry, it implies not only assuming a process of transformation in its actions, but, above all, continuous learning. Technological innovation imposes new forms of consumption whose logic corresponds to new systems for the production, distribution and commercialization of information, culture, science and entertainment. Object of study. Adaptation of the radio medium to the digital ecosystem of audiences invites us to focus the attention of researchers on the media’s use of web-radio, app–radio and social media; the relevance of sound semiotics compared to other components of the message on users’ screens; and the alterations suffered by the business model and productive routines of the radio. Methodology. This research took as its focus of study three Colombian radio stations and their informative stations—Caracol Radio, W Radio, Blu Radio, RCN Radio and La FM—through a mixed methodology. Quantitative instruments—numerical data to monitor activities on social platforms—and qualitative instruments—interpretation of messages and visual composition of the message—allow for the monitoring and analyzing of the performance of the radio medium in the digital environment, and the tactical approach of radio agents to delineate the strategies that promote the expansion, positioning and participation of radio in the Colombian media ecosystem. Results. Normalization of connectivity, ubiquity, timelessness and interactivity are, today, inherent values of the content broadcast by the radio industry, which needs to appropriate the tastes and interests of the audience through multi-device, multi-tasking and multi-user devices. Conclusion. Consumption actions of listeners: users are concentrated on the Smartphone screens, which provides a habit of listening and monitoring that forces the media to incorporate the format—and language—of video into their productive dynamics in order to attract and retain the attention of their audiences.